Polymer-in-Ceramic Nanocomposite Solid Electrolyte for Lithium Metal Batteries Encompassing PEO-Grafted TiO2 Nanocrystals. Issue 7 (13th March 2020) - Colombo, Francesco; Bonizzoni, Simone; Ferrara, Chiara; Simonutti, Roberto; Mauri, Michele; Falco, Marisa; Gerbaldi, Claudio; Mustarelli, Piercarlo; Ruffo, Riccardo
Abstract : Lithium Metal Batteries (LMB) require solid or quasi-solid electrolytes able to block dendrites formation during cell cycling. Polymer-in-ceramic nanocomposites with the ceramic fraction exceeding the one normally used as the filler (>10 ÷ 15 wt%) are among the most interesting options on the table. Here, we report on a new hybrid material encompassing brush-like TiO2 nanocrystals functionalized with low molecular weight poly(ethylene oxide) (PEO). The nanocomposite electrolyte membranes are then obtained by blending the brush-like nanocrystals with high molecular weight PEO and LiTFSI. The intrinsic chemical compatibility among the PEO moieties allows a TiO2 content as high as ∼39 wt% (90:10 w/w functionalized nanocrystals/PEO-LiTFSI), while maintaining good processability and mechanical resistance. The 50:50 w/w nanocomposite electrolyte (18.8 wt% functionalized TiO2 ) displays ionic conductivity of 3 × 10 −4 S cm −1 at 70 °C. Stripping/plating experiments show an excellent long-term behavior even at relatively high currents of 200 μ A cm −2 . Upon testing in a lab-scale Li/electrolyte/LiFePO4 cell, the material delivers 130 mAh g −1 and 120 mAh g −1 after 40 and 50 cycles at 0.05 and 0.1 mA, respectively, with Coulombic efficiency exceeding 99.5%, which demonstrates the very promising prospects of these newly developed nanocomposite solid electrolyte for future development of LMBs.